Gipoventiljacionnaja trenirovka i sportivnaja rabotosposobnost' - Fudin, N. A.; Klassina, S. Ya.; Pigareva, S. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
In the work investigates voluntary regulation of breathing in combination with physical exercises in athletes. The study involved 3 groups of highly qualified athletes who trained in middle distance running. Group 1 (control) trained according to the standard athlete's methodology. Group 2 - for an arbitrary decrease in breathing rhythm during physical exercises (inspiration-expiration-pause 5-7 seconds). Group 3 - using hypoventilation breathing in combination with physical exercises (running distance segments against the background of maximum breath holding). It was found that the proposed hypoventilation training and especially their combination with physical exercises in athletes of the 3 group gave a pronounced positive dynamics of functional indicators, ensuring the achievement of higher sports results. Higher indices in the athletes of the 3 group were directly associated with combined hypoventilation training, when the consciously imposed motor and respiratory hypoxia, repeatedly summed up and repeated, formed stable compensatory relationships in the body, which ensured higher working capacity and efficiency.